Song of song s a close reading - Barbiero, Gianni, 1944- (Vetus Testamentum, Supplements, 2011)
This book puts forward an interpretation of the Canticle which is alert to the literal sense of the poem. The author thus distances himself both from the allegorical interpretation and from an interpretation that is purely secular. According to the author, the Song offers a theological vision of human love. Barbiero sees the Song as composed in the third century BC, in the Hellenistic epoch, but also as hugely dependent on the love poetry of the Ancient Near East, particularly that of Egypt. Above all, however, the Song was composed in dialogue with the other books of the Old Testament, especially in contrast with the negative view of sexuality which they represent. The study pays particular attention to the structure of the poem and of the individual cantos: for Barbiero, the Song is a closely unitary work and is only to be understood as a whole.